USM TO PROPOSE DEVELOPMENT MODEL FOR KEDAH ARCHAEOLOGICAL SITE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
SUNGAI BATU, KEDAH, 17 May 2017 – Universiti Sains Malaysia (USM), through the Centre for Global Archaeological Research (CGAR), will be forwarding a proposal on the development plan of the Kedah archaeological site in Sungai Batu, near Sungai Petani.